Enhanced T Cell Responses Induced by a Necrotic Dendritic Cell Vaccine, Expressing HCV NS3 - Mekonnen, Zelalem A.; Masavuli, Makutiro G.; Yu, Wenbo; Gummow, Jason; Whelan, Dawn M.; Al-Delfi, Zahraa; Torresi, Joseph; Gowans, Eric J.; Grubor-Bauk, Branka (Frontiers in Microbiology, 2020)
A vaccine that induces potent, broad and sustained cell-mediated immunity, resulting in effective memory has the potential to restrict hepatitis C (HCV) virus infection. Early, multi-functional CD4+ and CD8+ T cell responses against non-structural protein 3 (NS3) have been associated with HCV clearance. Necrotic cells generate strong immune responses and represent a major antigenic source used by dendritic cells (DC) for processing and presentation, but there is conflicting evidence as to their immunogenicity in vaccination. Immunization with DC loaded with viral antigens has been done in the past, but to date the immunogenicity of live vs. necrotic DC vaccines has not been investigated. We developed a DC2.4 cell line stably expressing HCV NS3, and compared the NS3-specific responses of live vs. necrotic NS3 DC. Vaccination of mice with necrotic NS3 DC increased the breadth of T-cell responses and enhanced the production of IL-2, TNF-α, and IFN-γ by effector memory CD4+ and CD8+T cells, compared to mice vaccinated with live NS3 DC. A single dose of necrotic NS3 DC vaccine induced a greater influx and activation of cross-presenting CD11c+ CD8α+ DC and necrosis-sensing Clec9A+ DC in the draining lymph nodes. Furthermore, using a hydrodynamic challenge model necrotic NS3 DC vaccination resulted in enhanced clearance of NS3-positive hepatocytes from the livers of vaccinated mice. Taken together, the data demonstrate that necrotic DC represent a novel and exciting vaccination strategy capable of inducing broad and multifunctional T cell memory.